AMPKβ isoform expression patterns in various adipocyte models and in relation to body mass index - Kopietz, Franziska; Degerman, Eva; Göransson, Olga (Frontiers in Physiology, 2022)
AMP-activated protein kinase (AMPK) activation is considered a useful strategy for the treatment of type 2 diabetes (T2D). It is unclear whether the expression and/or activity of AMPK in adipocytes is dysregulated in obesity. Also, the expression/activity pattern of AMPKβ isoforms, which are targets for AMPK activators, in adipocytes remains elusive. In this study we show that the two AMPKβ isoforms make roughly equal contributions to AMPK activity in primary human and mouse adipocytes, whereas in cultured 3T3-L1 adipocytes of mouse origin and in primary rat adipocytes, β1-associated activity clearly dominates. Additionally, we found that obesity is not associated with changes in AMPK subunit expression or kinase activity in adipocytes isolated from subcutaneous adipose tissue from individuals with various BMI.